PENGARUH MOTIVASI KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA GURU SMP NEGERI SE-KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Soni Yarsi; Isjoni, Elvis Suanto (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
Teachers as an educator up to now are still not following the rules and needs. Based on the interview results with school principals, the teacher performance of Public Junior High School teachers throughout the Bagan Sinembah District in Rokan Hilir are faced with various problems, they are the teacher's work motivation and organizational climate. The research in this article is to determine and prove that there was an effect of work motivation and organizational climate on teacher performance at SMP Negeri Sinembah in Rokan Hilir. The research population involved 117 teachers who teach at Public Junior High School in Bagan Sinembah Rokan Hilir. Whilst, the sampling technique, which was selected from the population, used Cluster Random Sampling. The research data were obtained by using a questionnaire. The research was quantitative research. The methods used were descriptive statistical methods and inferential statistical methods with parametric statistical techniques. The research outcome showed that there was a positive and significant effect of work motivation on teacher performance at Public Junior High Schools in Bagan Sinembah Rokan Hilir, which was 47.6%. Subsequently, there was a positive and significant effect of organizational climate on teacher performance, which was 42.5%. In addition, there was a positive and significant effect of work motivation and organizational climate on teacher performance, which was 53%.